bahasa inggris - Ardelia, Berliani; Irmanopaliza, Ade; Hastuti , Windi; Setyaningsih, Nining; Sutarni, Sri (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Good learning design is a learning design that is adjusted to the needs of students in order to achieve the learning objectives that have been set. This study aims to analyze students' understanding of mathematical concepts in Realistic Mathematic Education learning with students who do not apply hypothetical learning trajectory to trigonometric comparison material. Quantitative research method with phonomology design. The subjects of this study were 28 students of class X IPA at SMA 1 Boyolali. The data and data sources in this study consisted of the results of observations of test answers, and interview results. Data collection techniques from written test results (diagnostic tests), interviews and observations. The results of the study obtained the results of the Mann-Whitney test on the post-test value data showed a significance value of 0.000 on students' conceptual understanding. This significance value is smaller than the significance level of α = 0.05 so that there is a significant difference in the average value of conceptual understanding between the experimental and control classes. So it can be concluded that students in the experimental class who were given mathematics learning treatment using RME-based HLT had a better conceptual understanding than students in the control class who were not given treatment.